Implementasi Metode Pembelajaran Resitasi Dalam Meningkatkan Motivasi Belajar Siswa Pada Mata Pelajaran PAI - Pernandes, Rapi; Wirdati, Wirdati (Prodi Pendidikan Keagamaan Islam, 2024)
This research aims to determine the use of the recitation method in increasing student learning motivation in PAI subjects at SDN 26 Jati Utara. This research uses a qualitative method with a descriptive approach. This research was carried out at SDN 26 Jati Utara. Data collection techniques used were observation, documentation and interviews. The results of this research show that: (1) the planning of the recitation method in Islamic religious education subjects in increasing students' learning motivation in the final day material at SDN 26 Jati Utara is guided by the curriculum which can be seen in the form of lesson plans. (2) At the stage of implementing the recitation method in Islamic Religious Education subjects in increasing students' learning motivation for final day material at SD Negeri 26 Jati Utara, the teacher has fulfilled the syntax of the recitation method, namely preparing learning materials, delivering the material and providing stimulus and response to students, giving assignments to students, accountability for assignments and conducting evaluations. (3) There are 2 forms of student learning motivation using the recitation method, namely intrinsic motivation in the form of challenge, curiosity, self-control and fantasy. Meanwhile, extrinsic motivation takes the form of parental sanctions, gifts, punishment and praise. (4) Evaluation of the recitation method shows that PAI teachers do not use observation sheets for assessing student discussion results listed in the RPP and the teacher uses a multiple choice written test where the form of the questions presented does not meet the HOTS question criteria, so it is not well tested to increase motivation. student learning during the recitation method learning process in class V of SDN 26 Jati Utara.